(3GdGfJUGQ deG LQO aj GdePGgH ef GdCNHGQ hGdGNJjGQs - (3YHO Gddg GHf eMeO Hf gHg Gddg GHf GdeWgQ Hf CHi YUQhf GdehUdj GdTGaYj, TQa GdOjf, CHh SYjO, J (B585 (3g` s
(3ChdgG (B:s
(3cJGH GdLfGjGJ s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3ef fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B288 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdaGJM (B(1493) s
Keywords: (3Gdabg GdTGaYjs